Using Thai folktales to improve Chinese students’ reading and writing skills - Buranakorn, Patcharin (Academic and Research Journal of Liberal Arts (Online), 2022)
This research project looks at the use of Thai folktales to improve Chinese students’ reading and writing skills in Thai language at Huachiew Chalermprakiat University. The research shows that when students learn from 10 drill patterns that improve reading and writing skills, their learning achievements are greater. For example, it helps students learn how to read for main ideas and how to write summaries. The research shows that students become more efficient at these skills. Moreover, Thai folktales make reading enjoyable. Both children and adults love reading and listening to tales. Apart from readers’ pleasure, Thai folktales offer other advantages, such as improving language skills by focusing on the use of words, proverbs, and thoughts. Thus, Thai folktales are a very useful tool for developing Chinese students’ Thai language skills, particularly for beginners. At all levels, the study of Thai fairy tales increases students’ endurance, loyalty, passion, interest, and good attitudes when learning the Thai language.